Who can Profit from Dance? An Exploration of Copyright Ownership. (May 2017) - Pavis, Mathilde; Waelde, Charlotte; Whatley, Sarah
Abstract : Focusing on UK copyright law, this article explores ownership of the dance by reference to the work of disabled dance artists. Our attention is on this group because their position within the dance workforce has always been precarious and so perhaps have most to gain through greater recognition of authorship in their work. Through an examination of the law as it applies to two different projects featuring Caroline Bowditch, we suggest that, contrary to the views of some, the performers are either authors of the copyright in the arrangement of the dance on their bodies, or joint authors in the work of dance. This is important because the author is the first owner of copyright in a dance; income from exploitation generally flows to the owner. With the rise of social media there may be yet further opportunities for exploiting dance. Starting from a doctrinal legal perspective, and bringing together dance and law to explore the vexed questions of cultural value, audience literacy and commercial exploitation, we hope to bring attention to the labour of disabled dance artists and the different ways in which all dancers can assert the rights to their work. In taking this approach this contribution differs from recent scholarship on dance and law, most notably works by Anthea Kraut, Choreographing Copyright: Race, Gender, and Intellectual Property Rights in American Dance (Oxford University Press, 2015) and Caroline Picart, Critical Race Theory and Copyright in American Dance: Whiteness as Status Property (Springer 2013). These analyses examine dance and American copyright law through race and gender lenses. Reading across the contributions would suggest that the time is ripe for a truly interdisciplinary project in which experts from law, dance and, disability studies come together to deepen and extend our knowledge and understanding of this area.